PERANCANGAN DESIGN OF A PWA-BASED DAILY ACTIVITY REPORT MONITORING INFORMATION SYSTEM IN THE REGENT'S OFFICE OF BANTAENG DISTRICT: DESIGN OF A PWA-BASED DAILY ACTIVITY REPORT MONITORING INFORMATION SYSTEM IN THE REGENT'S OFFICE OF BANTAENG DISTRICT - Ismi, Nur; Erfina; Ibrahim, Firmansyah (Prodi Sistem Informasi UIN Alauddin, 2024)
Utilization of information technology by government institutions also using a monitoring system known as E-Government is an important part of government sustainability. The obstacle faced by each section head is during the process of making monthly reports, where when making monthly reports activities are often not recorded in the agenda book. To overcome this problem, we need a system that can record the daily activities of each section head systematically and accurately. The system that can solve the above problems is a website system, Progressive Web Apps (PWA) is a concept for implementing website creation that applies technology by building applications using the PWA concept which will make web applications run on various platforms such as websites, desktops, and mobile or Android platforms. Based on the percentage value of the question indicators, the System Usability Scale test results were 80.1 and received a